Commercial Interests, the Technological Imperative, and Advocates: Three Forces Driving Genomic Sequencing in Newborns - Pereira, Stacey (The Hastings Center report, 2018)
While the NSIGHT program was driven by a desire to define and gather data about both the benefits and harms of introducing genomic sequencing into the care of newborns, it remains to be seen how much influence these data will have in shaping the use of this technology in newborns. Ultimately, three additional forces—commercial interests, the technological imperative, and advocates—may play a significant role in shaping the use of sequencing in newborns. Policy-makers and clinicians should be aware of the effects of these additional forces when considering the appropriate use of this technology in clinical practice and public health screening programs.